Depression, anxiety and stress, comorbidity evaluation among a large sample of general adults: results from SEPAHAN study - Moluk Hadi Alijanvand; Awat Feizi; Hamid Afshar; Hamidreza Roohafza; Ammar Hassanzadeh Keshteli; Peyman Adibi (Universidade Estadual de Maringá, 2022)
Depression, anxiety and stress are common psychological disorders (PDs). This study aimed to assess the odds of co-occurrence of mentioned PDs in total sample and different levels of socio-demographic characteristics, specifically among a large sample of general adults. In a cross-sectional, community-based study conducted among 4763 Iranian adults, depression and anxiety were assessed with Hospital Anxiety and Depression Scale (HADS) and stress with General Health Questionnaire (GHQ). The loglinear analysis was applied to investigate their comorbidities. Based on selected models with pair-comorbidity of anxiety with stress, depression with stress, and anxiety with depression, the results showed the odds of comorbidity between anxiety and depression (odds ratio (OR) =12.29, 95%CI: 9.58-15.80), depression and stress (OR = 7.80, 95%CI: 6.55-10.18), and stress and anxiety (OR = 4.62, 95%CI: 3.71-5.75). Also, ORs of pair-comorbidities were the same, except between stress and anxiety for men compared to women (adjusted-OR = 6.47, 95%CI: 4.44-9.49 versus 3.85, 95%CI: 2.95-5.00) and comorbidity between stress and depression for the participants with lower than 40 years compared to others (adjusted-OR = 9.03, 95%CI: 7.17-11.36 versus 6.41, 95%CI: 4.90-8.41), p< 0.05. Stress comorbidity with depression was higher level than other pair-comorbidities. Obvious discrepancies were also observed in terms of ORs of pair-comorbidities between three mentioned disorders in different levels of SDCs.